GMS: Grid-Based Motion Statistics for Fast, Ultra-Robust Feature Correspondence - JiaWang Bian; Wen-Yan Lin; Matsushita, Yasuyuki; Sai-Kit Yeung; Tan-Dat Nguyen; Ming-Ming Cheng (2017 IEEE Conference on Computer Vision and Pattern Recognition (CVPR), 2017)
Incorporating smoothness constraints into feature matching is known to enable ultra-robust matching. However, such formulations are both complex and slow, making them unsuitable for video applications. This paper proposes GMS (Grid-based Motion Statistics), a simple means of encapsulating motion smoothness as the statistical likelihood of a certain number of matches in a region. GMS enables translation of high match numbers into high match quality. This provides a real-time, ultra-robust correspondence system. Evaluation on videos, with low textures, blurs and wide-baselines show GMS consistently out-performs other real-time matchers and can achieve parity with more sophisticated, much slower techniques.